Correlating alkali-silica reaction (ASR) induced expansion from short-term laboratory testings to long-term field performance: A semi-empirical model. (November 2022) - Nguyen, Thuc Nhu; Sanchez, Leandro F.M.; Li, Jianchun; Fournier, Benoit; Sirivivatnanon, Vute
Abstract: Correlating short-term expansion of concrete specimens in the laboratory and long-term expansion of concrete in the field is crucial to evaluate the reliability of laboratory test methods and essential for the prognosis of alkali-silica reaction (ASR) in concrete infrastructures. In this study, a novel semi-empirical approach is proposed for forecasting ASR-induced expansion of unrestrained concrete in the field using laboratory measurements data. In addition to the use of short-term laboratory expansion data, the model accounts for the effects of alkali leaching, alkali contribution from aggregates, and environmental conditions (i.e., temperature and relative humidity). A comprehensive database from the literature was gathered for the development and calibration of the proposed model. Finally, the model was used for various concrete blocks incorporating different reactive aggregates and exposed to three outdoor conditions in Canada and the USA. Model outcomes show that it is highly promising for forecasting the induced expansion of concrete in the field from the accelerated laboratory tests data. Analysing the modelling results also highlights the importance of alkali leaching and environmental conditions on the correlation between laboratory and field performance.